BLOCKCHAIN-BASED AMPLIFICATION OF CLOUD SECURITY (International Journal of Food and Nutritional Sciences, 2022)
In the internet-dependent world, the demand for data is increasing day by day. This has generated an issue of massive data storage. To overcome this issue, a cloud-based storage service was developed. Today there is extensive involvement of cloud on business transactions and daily applications. This has raised the need to provide high end of security to the stored data; the project helps overcome this problem. The use of a blockchain network as an interface to access the data will help overcome the security of data on the cloud. The blockchain is a distributed public ledger and Internet-based computer network. The proposed system works on the ERP data of a company, on a private cloud, which is accessible through the internet from any place. It validates and secures the employee data of the company. Smartphone and laptop security features like biometrics and password validation can be to make this idea more robust and easier to use for end-user. The local validation process of laptops and smartphones acts as a user interface between the background and the user. This also acts as the next level of security for validation of user details. Thus, providing a more secure way of accessing the cloud service.